Formulation of gluten-free bread using psyllium husk and chia seed seen from physical and sensory characteristics - Rahardjo, Monika; Sihombing, Monang (AGROMIX, 2025)
Introduction: Gluten-free bread is a type of bread product made without gluten, and its consumption has increased in recent years, especially for individuals with celiac disease or driven by health considerations. The absence of gluten in gluten-free bread presents challenges in achieving the desired texture and structure. The incorporation of psyllium husk and chia seed into gluten-free bread formulations offers numerous benefits, both in terms of improving the bread's physical properties. Therefore, this study aims to find gluten-free bread formulations from a mixture of psyllium husk and chia seed seen from physical and sensory characteristics. Methods: This research method consists of the making of gluten-free bread, physical analysis (texture), sensory analysis, and statistical analysis. Results: For physical characteristics, psyllium husk, and chia seed incorporation affect springiness index, chewiness, adhesive force, and adhesiveness parameters in gluten-free bread, while for sensory characteristics several parameters have significant differences, namely aroma, taste, texture, and overall parameter, meanwhile appearance parameter has no significant difference. For the overall parameter, gluten-free bread with only psyllium husk (Formulation 1) received the highest rating preferred by the panelist. Conclusion: The incorporation of psyllium husk and chia seed affects the physical and sensory characteristics of gluten-free bread.